Prevalence of falls among community-dwelling elderly and its associated factors: A cross-sectional study in Perak, Malaysia - Yeong, U.Y.; Tan, S.Y.; Yap, J.F.; Choo, W.Y. (Academy of Family Physicians of Malaysia, 2016)
Introduction: Fall is a major cause of injuries and can increase the risk of early mortality among elderly. The objective of this study was to determine the prevalence of falls among community-dwelling elderly in rural Malaysia and its associated factors. Methods: Data were obtained from a cross-sectional survey in five randomly selected districts in the state of Perak, Malaysia. A total of 250 households were randomly selected. A total of 811 individuals aged 60 years or more were recruited and interviewed using a structured questionnaire. Information about socio-demographic, history of falls in the past 1 year, medical history, drug history and physical activity level were enquired. Results: The prevalence of falls in the past 1 year among community-dwelling elderly was reported to be 4.07%. Indigenous elderly (Adjusted odd ratio, AOR = 6.06, 95% CI = 1.10-33.55, p = 0.039) and living alone (AOR = 2.60, 95% CI = 1.04-6.50, p = 0.042) were shown to be factors associated with falls. Physical activity level, number of co-morbidities and number of medications used were not associated with falls. Conclusion: Elderly of indigenous ethnicity and living alone are the main factors associated with falls in this population. Indigenous people may be at higher risk, which warrant further investigation with a larger sample to improve the precision of estimates.